Aula communitatis: the community hall in England, c. 1400-1640 - Weir, J (2020)
This thesis examines the architectural and contextual connections between twenty-nine extant late medieval and early modern community buildings to establish whether they are sufficiently similar to be identified as a single building type. The buildings are located across different regions of England, the South West and East Anglia, and demonstrate a whole range of historical and modern designations, including ‘church houses’, ‘guildhalls’, ‘town halls’, and ‘market houses’. Though the buildings are predominantly in rural settings, several in small towns are included. Together with the more frequently studied town halls and market halls of larger towns and cities, particularly from the second half of the sixteenth century onwards, these permit an assessment of whether the building type can be applied across the town/country divide. Though buildings remain the primary source, the value of documentary and historical visual records is considered for their ability to provide images of lost or altered buildings, or details as to construction, plan-form, and use.